Molecular Detection of Sus scrofa DNA Using IGF2 Gene Primers as Proof of Concept for Sybr Green-based Qualitative Real-time PCR - Raden Rara Bhintarti Suryohastari; Muhammad Saltes Albiansyah; Rizky Intan Novianti; Siti Hajar Hijriyah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Detection of porcine (Sus scrofa) DNA is essential for halal meat authentication and requires highly specific and reproducible molecular assays. This study evaluated insulin-like growth factor 2 (IGF2) gene primers as a proof of concept for qualitative detection using SYBR Green-based real-time PCR. The IGF2 locus was selected due to its interspecies sequence divergence and reported specificity to Sus scrofa. Qualitative analysis included Sus scrofa DNA, Bos taurus DNA as a non-target control, and a no-template control (NTC). Conventional PCR identified 58 °C as the optimal annealing temperature. In real-time PCR, Sus scrofa DNA was consistently detected with a mean cycle threshold (Ct) of 29.22 ± 0.11 and a low coefficient of variation (CV) of 0.38% across three technical replicates, indicating high intra-assay precision. Melting curve analysis yielded a single, well-defined peak with a melting temperature (Tm) of 80 °C, supporting the amplicon's specificity. These findings supported the development of feasible IGF2 primers for the qualitative detection of Sus scrofa DNA using real-time PCR with shorter amplicons, which served as a foundation for further validation of the qPCR assay.